City-university relationship. Dilemmas of two opposing cultures. The case of Osorno and the University of Los Lagos (Revista LIDER, 2021)
Throughout history (1965-2005) the link between the community of Osorno and the Universidad de los Lagos has developed as a dialectic process– attachment/separation, inclusion – exclusion, and belonging/ detachment. This has given rise to varied viewpoints and opinions from the different individuals participating in this relationship both at the community and University level. Thorough the construction of a real, concrete and measurable history, this university - community relationship of debilitating and facilitating elements has led to the emergence of answers that have dissolved previous dilemmas. Within this context, the relation between the University and the city is a difficult dilemma to and dress and analyze. In this case, some relative questions are: How does University community perceive their role within the community ?. Furthermore, does the community of Osorno recognize the University as a pertinent institution, capable of facing it’s problems and obstacles ? These are difficult questions to answer, especially taking into account the distinct cultures between the community and the University, including their history, beliefs, values and myths.